2014
DOI: 10.1088/1367-2630/16/12/125003
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the interplay between network structure and market effects in Bitcoin

Abstract: A main focus in economics research is understanding the time series of prices of goods and assets. While statistical models using only the properties of the time series itself have been successful in many aspects, we expect to gain a better understanding of the phenomena involved if we can model the underlying system of interacting agents. In this article, we consider the history of Bitcoin, a novel digital currency system, for which the complete list of transactions is available for analysis. Using this datas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 18 publications
0
68
0
1
Order By: Relevance
“…The user transaction network can be extracted from the blockchain by exploiting the fact that initiating a transaction with multiple inputs requires signing it with the private keys of all input addresses. This implies that all of these addresses are controlled by the same entity [1, 21,28] that we simply call a user. Similar as in literature [21,28], we process hundreds of gigabytes of Bitcoin blockchain data by merging all addresses that belong to the same user.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The user transaction network can be extracted from the blockchain by exploiting the fact that initiating a transaction with multiple inputs requires signing it with the private keys of all input addresses. This implies that all of these addresses are controlled by the same entity [1, 21,28] that we simply call a user. Similar as in literature [21,28], we process hundreds of gigabytes of Bitcoin blockchain data by merging all addresses that belong to the same user.…”
Section: Methodsmentioning
confidence: 99%
“…al. [21] demonstrated that there exists a certain correlation between the Bitcoin network structure and the market effects i.e. Bitcoin price change, up to early 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 lists summary statistics of the datasets, and we briefly describe them below. Each dataset is a collection of timestamped directed [26]. Timestamps are the creation time of the block on the blockchain containing the transaction.…”
Section: Computational Experimentsmentioning
confidence: 99%
“…Methods from statistical physics are also valuable to analyze the dynamics of general economic networks. Kondor et al show analyze the network of transactions of the digital currency system Bitcoin [31]. They show that the evolution of a macroscopic quantity, the market price, can be recovered from rather little information about the microscopic structure of the trading network.…”
Section: Theoretical and Practical Progessmentioning
confidence: 99%